Konsep Tanggung Jawab Sosial Perusahaan Melalui Pendekatan Filsafat Hukum Islam - Satria Sukananda (Lex Renaissance, 2019)
Almost all theories, concepts, and practices of CSR are based on cultural values, ethics and beliefs of the western societies, especially Europe and America. Although the concept of CSR is not necessarily fully practiced by companies in all countries, especially for those that have different ethics, cultures and beliefs, such as Islamic companies. The problem that becomes the focus of the study in this research is the concept of CSR which is examined through the philosophical approach of Islamic law. This study applies a normative legal research method with both legislative and conceptual approach. The results show that CSR, when examined through the approach of Islamic legal philosophy with the methods of ta'lili and the Qiyas ijtihad, is indicated that the concept of social responsibility had long existed in Islam even though the Western concept of CSR had only emerged in the fourth wave of business principles in the 1930s. Therefore, the principle of social responsibility that has been outlined in the Al-Qur'an and Sunnah must be used as a guidance for the lives of Muslims in various activities including in Islamic business.